Novel Insights Into Molecular Mechanism of Mitochondria in Diabetic Cardiomyopathy - Bai, Jing; Liu, Chuanbin; Zhu, Pingjun; Li, Yang (Frontiers in Physiology, 2021)
Cardiovascular complication is one of the significant causes of death in diabetic mellitus, in which diabetic cardiomyopathy, independent of hypertension, cardiac valvular disease, and coronary atherosclerosis, occupies an important position. Although the detailed pathogenesis of diabetic cardiomyopathy remains unclear currently, mitochondrial morphological abnormality and dysfunction were observed in diabetic cardiomyopathy animal models according to much research, suggesting that mitochondrial structural and functional impairment played an integral role in the formation of diabetic cardiomyopathy. Thus, we have summarized the effect of mitochondria on the process of diabetic cardiomyopathy, including abnormal mitochondrial morphology, mitochondrial energy metabolism disorder, enhanced mitochondrial oxidative stress, mitochondrial unbalanced calcium homeostasis and mitochondrial autophagy. Based on the above mechanisms and the related evidence, more therapeutic strategies targeting mitochondria in diabetic cardiomyopathy have been and will be proposed to delay the progression of the disease.